Altered Brain Function in Treatment-Resistant and Non-treatment-resistant Depression Patients: A Resting-State Functional Magnetic Resonance Imaging Study - Sun, Jifei; Ma, Yue; Chen, Limei; Wang, Zhi; Guo, Chunlei; Luo, Yi; Gao, Deqiang; Li, Xiaojiao; Xu, Ke; Hong, Yang; Hou, Xiaobing; Tian, Jing; et al. (Frontiers in Psychiatry, 2022)
Objective: In this study, we used amplitude of low-frequency fluctuation(ALFF) and regional homogeneity (ReHo) to observe differences in local brain functional activity and its characteristics in patients with treatment-resistant depression (TRD) and non-treatment-resistant depression (nTRD), and to explore the correlation between areas of abnormal brain functional activity and clinical symptoms. Method:Thirty-five patients with TRD, 35 patients with nTRD, and 35 healthy control (HC) were included in resting-state fMRI scans. ALFF and ReHo were used for image analysis and further correlation between abnormal brain regions and clinical symptoms were analyzed. Results：ANOVA revealed that the significantly different brain regions of ALFF and ReHo among the three groups were mainly concentrated in the frontal and temporal lobes.Compared with the nTRD group, the TRD group had lower ALFF in the left/right inferior frontal triangular gyrus, left middle temporal gyrus, left cuneus and bilateral posterior lobes of the cerebellum, and higher ALFF in the left middle frontal gyrus and right superior temporal gyrus, and the TRD group had lower ReHo in the left/right inferior frontal triangular gyrus, left middle temporal gyrus, and higher ReHo in the right superior frontal gyrus.Compared with the HC group, the TRD group had reduced ALFF/ReHo in both the right inferior frontal triangular gyrus and the left middle temporal gyrus.Pearson correlation analysis showed that both ALFF and ReHo values in these abnormal brain regions were positively correlated with HAMD-17 scores (P<0.05). Conclusion:Although the clinical symptoms were similar in the TRD and nTRD groups, abnormal neurological functional activity were present in some of the same brain regions.Compared with the nTRD group, ALFF and ReHo showed a wider range of brain area alterations and more complex neuropathological mechanisms in the TRD group, especially in the inferior frontal triangular gyrus of the frontal lobe and the middle temporal gyrus of the temporal lobe.